Optimal Power Flow Based Economic Generation Scheduling in Day-ahead Power Market - Kshitij Choudhary; Rahul Kumar; Dheeresh Upadhyay; Brijesh Singh (International Journal of Applied Power Engineering (IJAPE), 2017)
The present work deals with the economic rescheduling of the generation in an hour-ahead electricity market. The schedules of various generators in a power system have been optimizing according to active power demand bids by various load buses. In this work, various aspects of power system such as congestion management, voltage stabilization and loss minimization have also taken into consideration for the achievement of the goal. The Interior Point (IP) based Optimal Power Flow (OPF) methodology has been used to obtain the optimal generation schedule for economic system operation. The IP based OPF methodology has been tested on a modified IEEE-30 bus system. The obtained test results shows that not only the generation cost is reduced also the performance of power system has been improved using proposed methodology.